Reassessing Article 51 of the Indonesian Competition Law Through the KPPU Decision No. 13/KPPU-I/2014 - Jingga Ardeanti Putri; Iwan Erar Joesoef (Universitas Semarang, 2025)
This study analyses the principle of legal certainty in direct appointment practices conducted by State-Owned Enterprises (BUMN) within the framework of Indonesian business competition law, using the KPPU Decision No. 13/KPPU-I/2014 involving PT Angkasa Pura I and PT ExecuJet Indonesia as a case study. The research examines the tension between the monopoly exemption granted to BUMN under Article 51 of Law No. 5 of 1999 and its obligation to uphold fair competition in the procurement process. A normative juridical method was employed, combining statutory and case study approaches, with secondary data analysed qualitatively. The findings reveal that although Article 51 allows BUMN to operate monopolies in sectors related to essential services, the direct appointment of PT ExecuJet Indonesia by PT Angkasa Pura I constituted conduct inconsistent with the principles of fair competition. The transaction failed to satisfy transparency and accountability requirements, thereby creating legal uncertainty in the procurement mechanism. This study concludes that the current regulatory framework does not sufficiently prevent anti-competitive behaviour by BUMN when exercising monopoly privileges. Therefore, a reformulation of procurement policies is required to align BUMN practices with the principles of legal certainty, transparency, and fair business competition. The study contributes to the development of competition law discourse by highlighting the regulatory gaps in the intersection between monopoly exemptions and procurement governance.